Health-related quality of life profile of Indonesian children and its determinants: a community-based study - Mei Neni Sitaresmi; Braghmandita Widya Indraswari; Nisrina Maulida Rozanti; Zena Sabilatuttaqiyya; Abdul Wahab (BMC, 2022)
Abstract Background Assessing health-related quality of life (HRQOL) and its determinants in children may provide a comprehensive view of child health. The study aimed to assess the HRQOL in Indonesian children and its determinants. Methods We conducted a community-based cross-sectional study in the Sleman District of Yogyakarta Special Province, Indonesia, from August to November 2019. We recruited children aged 2 to 18 years old using the Sleman Health and Demography Surveillance System sample frame. We used the validated Indonesian version of Pediatric Quality of life Inventory™ (Peds QL™) 4.0 Generic core scale, proxy-reports, and self-reports, to assess the HRQOL. Results We recruited 633 proxies and 531 children aged 2-18 years. The mean total score of self-report and proxy-report were 89.9+ 8.5 and 93.3 + 6.4. There was a fair to moderate correlation between self-reports and proxy-reports, with intra-class correlation ranging from 0.34 to 0.47, all p < 0.001. Half of the children (49.4% from proxy-report and 50.1% from self-report) reported having acute illness during the last month. Based on proxy-reports, multivariate regression analysis demonstrated lower HRQOL for children with acute health problems, younger age, history of low birth weight, abnormal delivery, lower fathers' educational level, and government-paid insurance for low-income families. Conclusion Sociodemographic determinants of a child's HRQOL, acute health problems, and low birth weight were associated with lower HRQOL in the general pediatric population. In low- and middle-income countries where acute infections and low birth weight are still prevalent, its prevention and appropriate interventions should improve child health.